THE URGENCY OF ORGANIZATIONAL CULTURE FOR THE DEVELOPMENT OF ISLAMIC EDUCATIONAL INSTITUTIONS - Sulistyorini, Sulistyorini (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Organizational culture, especially in Islamic educational institutions, plays a crucial role, as it makes the institution adaptable, flexible, and elastic, just like a culture that will never experience decline and becomes perfect when combined with a religion based on the Qur'an and Sunnah. This research uses a qualitative approach that involves the researcher as the research instrument. In data collection, the rector is the key informant. Other informants were selected using snowball sampling techniques. This process continued until data saturation. In addition to interviews, research data were collected through observation and written documents. The collected data were analyzed following the steps outlined by Miles and Huberman (1984), such as data reduction, data presentation, and drawing conclusions (illustration/verification). More specifically, data validation was done through triangulation. The research results show that the organizational culture that can develop UIN Sayyid Ali Rahmatullah is the religious culture, hardworking culture, and disciplined culture. The values that have developed include the values of Fastabiqul khaerat, Jihad, Uswah, and togetherness.